Behavior of concrete with in-plane hollow circular inclusion [electronic resource] - Mohd. Zulkarnaain Sulaiman, 1980-; Redzuan Abdullah, supervisor (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan ( Awam - Struktur)) - Universiti Teknologi Malaysia, 2007